Effects of recipient behaviour towards mobile banking performance in microfinance institutions / Afifa Malina Amran, Intan Salwani Mohamed and Sharifah Norzehan Syed Yusuf. - Amran, Afifa Malina; Mohamed, Intan Salwani; Syed Yusuf, Sharifah Norzehan (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2018)
The general agenda of microfinance is to extend financing facilities to the population in rural and remote areas, especially to the poor. However, distance and insufficient infrastructure have always been associated with conditions at remote areas. Access roads and public transportation to most remote areas are seldom maintained and are often in poor shape. These make it difficult for microfinance recipients to commute from their home to the bank. Consequently, this will result in inefficient communication where movement of information becomes slow and easily interrupted. As such, the current study investigates how microfinance recipient behaviour could affect implementation of mobile banking in microfinance institutions (MFIs). As a leading microfinance provider in Malaysia, Amanah Ikhtiar Malaysia (AIM) was selected as a case study for the current study. Usage of the M-Ringgit mobile banking was investigated to look into its current practices as well as recipient behaviour in making repayments using the M-Ringgit. The case findings demonstrate that no matter how sophisticated the M-Ringgit technology is, sahabats must be educated enough to use the M-Ringgit. Therefore, by giving M-Ringgit training to sahabats, AIM exercises its vicegerent duties in ensuring that sahabats are capable to use the M-Ringgit.